2015
DOI: 10.1088/0022-3727/48/33/335308
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and electrical properties of epitaxial NbO2thin film lateral devices

Abstract: Epitaxial NbO 2 (110) films, 20 nm thick, were grown by pulsed laser deposition on Al 2 O 3 (0001) substrates. The Ar/O 2 total pressure during growth was varied to demonstrate the gradual transformation between NbO 2 and Nb 2 O 5 phases, which was verified using x-ray diffraction, x-ray photoelectron spectroscopy, and optical absorption measurements. Electric resistance threshold switching characteristics were studied in a lateral geometry using interdigitated Pt top electrodes in order to preserve the epitax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 41 publications
0
46
0
Order By: Relevance
“…It is also possible to induce MIT in NbO 2 by applying an electric field, where joule heating produced by the applied electric field can easily cause this material to undergo a MIT. 9 Reversible threshold switching in current has been reported mostly using amorphous NbO 2 films, where the current turns off immediately after lowering the input voltage (V in ) below the threshold voltage (V th ). 3,[10][11][12][13] Current-voltage (IV ) characteristics usually exhibit current-controlled (s-type) negative differential resistance (dV /dI < 0) while switching from a low current semiconducting to a high current metallic state.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is also possible to induce MIT in NbO 2 by applying an electric field, where joule heating produced by the applied electric field can easily cause this material to undergo a MIT. 9 Reversible threshold switching in current has been reported mostly using amorphous NbO 2 films, where the current turns off immediately after lowering the input voltage (V in ) below the threshold voltage (V th ). 3,[10][11][12][13] Current-voltage (IV ) characteristics usually exhibit current-controlled (s-type) negative differential resistance (dV /dI < 0) while switching from a low current semiconducting to a high current metallic state.…”
mentioning
confidence: 99%
“…10,18,19 Previous reports on NbO 2 thin films have focused on a broad range of film qualities, ranging from amorphous 16,20 to epitaxial. 9,21,22 (100 nm)/Si wafers provided by Micron Technologies with nominal surface roughnesses < 0.5 nm were used as substrates for growth via pulsed laser deposition (PLD). The distance between the 99.99% purity NbO 2 target and substrate was 7.3 cm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we demonstrated that a 10‐nm‐thick NbO 2 seed layer improved the mobility of rutile SnO 2 thin films , which are promising for use as the transparent conductive electrodes of photovoltaic cells. Extensive studies on the use of NbO 2 thin films in electronic devices and fuel cells have been conducted. However, the performance of devices was mainly investigated in these studies; film growth and the physical properties of polycrystalline NbO 2 were not studied in detail .…”
Section: Introductionmentioning
confidence: 99%
“…50 nm of NbO2 was deposited over the electrodes via pulsed laser deposition at 700 o C substrate temperature in 2 mTorr Ar+O2 growth atmosphere with 1% O2 content using an NbO2 ceramic target (AJA International.). Film quality and thickness were assessed with x-ray photoelectron spectroscopy, x-ray diffraction, and x-ray reflectometry, confirming the major NbO2 phase, which forms with an additional top Nb2O5 layer of 2 nm due to air exposure [2]. STEM video was obtained simultaneously from 3 different detectors, collecting electrons at low (bright field or BF), intermediate (dark field or DF), and higher scattering angles (high-angle dark field or HDF).…”
mentioning
confidence: 97%